Systematic review of barriers and enablers to the delivery of palliative care by primary care practitioners. (October 2019) - Carey, Mariko L; Zucca, Alison C; Freund, Megan AG; Bryant, Jamie; Herrmann, Anne; Roberts, Bernadette J
Background: There is increasing demand for primary care practitioners to play a key role in palliative care delivery. Given this, it is important to understand their perceptions of the barriers and enablers to optimal palliative care, and how commonly these are experienced. Aim: To explore the type and prevalence of barriers and enablers to palliative care provision reported by primary care practitioners. Design: A systematic review of quantitative data-based articles was conducted. Data sources: Medline, Embase and PsychINFO databases were searched for articles published between January 2007 and March 2019. Data synthesis: Abstracts were assessed against the eligibility criteria by one reviewer and a random sample of 80 articles were blind coded by a second author. Data were extracted from eligible full-texts by one author and checked by a second. Given the heterogeneity in the included studies' methods and outcomes, a narrative synthesis was undertaken. Results: Twenty-one studies met the inclusion criteria. The most common barriers related to bureaucratic procedures, communication between healthcare professionals, primary care practitioners' personal commitments, and their skills or confidence. The most common enablers related to education, nurses and trained respite staff to assist with care delivery, better communication between professionals, and templates to facilitate referral to out-of-hours services. Conclusion: A holistic approach addressing the range of barriers reported in this review is needed to support primary care providers to deliver palliative care. This includes better training and addressing barriers related to the interface between healthcare services.